Functional analysis and operant treatment of food guarding in a pet dog. Issue 4 (10th May 2020) - Mehrkam, Lindsay R.; Perez, Brandon C.; Self, Victoria N.; Vollmer, Timothy R.; Dorey, Nicole R.
Abstract : The present study extended functional analysis (FA) methodology to human‐directed resource guarding in a dog in an in‐home setting. The subject underwent four conditions including control, attention, escape, and tangible, arranged in a modified FA. The results indicated multiply controlled resource guarding (i.e., escape, attention, and tangible functions). The experimenter then conducted a treatment evaluation involving three function‐based treatments in a concurrent multiple baseline design. Resource guarding decreased to zero levels in treatments for each maintaining contingency. Treatment effects were maintained when the subject was tested with an owner, with an untrained handler, a highly preferred treat, in an untrained setting, as well as after 2 weeks in the absence of training. Behavior analytic techniques may hold promise for lasting behavior change for resource guarding in domestic dogs, and should be examined in other populations and with other canine problem behavior.